2020
DOI: 10.1093/nar/gkaa750
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, chirality-dependent conformational and biological properties of siRNAs containing 5′-(R)- and 5′-(S)-C-methyl-guanosine

Abstract: Various chemical modifications have been identified that enhance potency of small interfering RNAs (siRNAs) and that reduce off-target effects, immune stimulation, and toxicities of metabolites of these therapeutic agents. We previously described 5′-C-methyl pyrimidine nucleotides also modified at the 2′ position of the sugar. Here, we describe the synthesis of 2′-position unmodified 5′-(R)- and 5′-(S)-C-methyl guanosine and evaluation of these nucleotides in the context of siRNA. The (R) isomer provided prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 64 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…Careful siRNA sequence selection, especially of seed regions, reduces the risk of hybridization-dependent off-target effects. Additional siRNA modifications, including glycol nucleic acid substitution in the seed region (ESC+) or altriol nucleic acid residues, might be implemented in future conjugates to further boost RNAi potency and curtail adverse effects 51,52 Chirality-dependent properties could also offer additional functionalities 53 . Balancing further chemical modifications and compatibility with RNAi machinery will be vital to the next generation of siRNA therapeutics.…”
Section: Galnac−sirna Conjugatesmentioning
confidence: 99%
“…Careful siRNA sequence selection, especially of seed regions, reduces the risk of hybridization-dependent off-target effects. Additional siRNA modifications, including glycol nucleic acid substitution in the seed region (ESC+) or altriol nucleic acid residues, might be implemented in future conjugates to further boost RNAi potency and curtail adverse effects 51,52 Chirality-dependent properties could also offer additional functionalities 53 . Balancing further chemical modifications and compatibility with RNAi machinery will be vital to the next generation of siRNA therapeutics.…”
Section: Galnac−sirna Conjugatesmentioning
confidence: 99%
“…The first FDA-approved siRNA therapeutic, Patisiran, is composed of multicomponent lipid nanoparticles (LNP) encapsulating partially chemically modified siRNA, in which some of the nucleotides are chemically modified at 2′-OMe. These chemical modifications reduce the nuclease degradation and innate immune system stimulation, while LNP provides the liver-specific delivery of siRNA via apolipoprotein E (ApoE) receptor endocytosis aside from nuclease protection [ 39 ].…”
Section: Ribonucleic Acid Interference (Rnai) Technologymentioning
confidence: 99%
“…Recently, Manoharan et al reported the synthesis and properties of C4 0 and C5 0 -modied nucleosides, such as the 4 0 -C-methoxy-modied nucleosides, (R)-, or (S)-5 0 -C-methyl-modied nucleosides. [14][15][16][17][18][19] These nucleosides enhanced the nuclease resistance of oligonucleotides, compared with C2 0 -modied nucleosides without thermally destabilizing RNA duplexes and inhibiting gene silencing activity. Moreover, (R)or (S)-5 0 -C-methylnucleosides improved the stability of oligonucleotides to snake venom phosphodiesterase (SVPD), compared with 4 0 -C-methoxy-nucleoside.…”
Section: Introductionmentioning
confidence: 99%